EVALUASI PENGGUNAAN ODOO UNTUK PEMBELAJARAN HRIS BAGI MAHASISWA PSIKOLOGI UNIVERSITAS ISLAM INDONESIA - Arief Fahmie; Annisaa Miranty Nurendra (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
The Human Resources Information System course at the Psychology Study Program at the Islamic University of Indonesia initially used SAP HCM, but the course management team decided to change the learning tool from SAP HCM to ODOO because it is free and open source. Continuing previous research on the usability of ODOO, this research aims to evaluate the implementation of ODOO usage. This evaluation research uses the CIPP model (context, input, process, product), which focuses on process (student assessment of lecturers) and product components (final grades of 2017, 2018, and 2020 students). The Academic Section collected the data then we analyzed it using descriptive statistics and ANOVA. The results showed that the performance of lecturers in the learning process was in the high category, while the average final score was at a sufficient level (B+). There is also no difference in student evaluations of lecturers in the three years. According to this study, HRIS learning with ODOO has been effective but needs improvement.